Modeling and inverse control of a compliant single-tendon-sheath artificial tendon actuator with bending angle compensation. (November 2019) - Shao, Ziyan; Wu, Qingcong; Chen, Bai; Wu, Hongtao; Zhang, Yuming
Abstract: Artificial tendon is a kind of bionic actuation system capable of imitating the transmission characteristics of skeleton tendon. This paper presents a new compliant single-tendon-sheath artificial tendon actuator inspired by Hill-type muscle model. The proposed artificial tendon can perform variable compliance properties with two linear springs applying onto the tendon-sheath element. Detailed development and modeling of the actuation system is given, and transmission characteristics are analyzed and validated via simulations and experiments. Then, a bending angle measurement method is developed to compensate the variation of tendon-sheath configuration during transmission process. A model-based inverse control strategy with bending angle compensation is developed for displacement and force control without distal feedback. Trajectory tracking experiments are conducted to verify the effectiveness of the proposed control strategy. Experimental results indicate that the control errors of displacement and force control without distal feedback could be limited within 7.07% and 13.62%, respectively.